Effects of Different Induced Molting Methods on the Performance of Commercial Layers - Amer, Mohammad Yasin; Khan, Sohail Hassan; Abbass, Muhammad Ismail; Abbass, Ghulam; Iftikhar, Naveed; Anwar, Muhammad; Amin, Muhammad; Anjum, Muhammad Yaqoob (Pakistan Journal of Nutrition, 2013)
A total of 1600 commercial strain (Nick Chick) Single Comb White Leghorn hens, 90 week of age, were used in this study to determine the effects of different induced molting programs on production and immune parameters. The hens were randomly divided into four treatment groups (three experimental and one control) of 400 hens each. The hens in the first treatment group were fed a layer ration containing 4 g/kg diet of C for 5 d and received a reduced photoperiod of 8 h/d for 5 d (Al2O3 group). In the second group, feed was withdrawn for 10 d, the photoperiod was reduced to 8 h/d and oyster shell and water were provided for ad libitum consumption. At Day 11, hens consumed corn and oyster shell ad libitum until Day 30 and at Day 31, hens was returned to a full feed layer ration and received 16 h of light/d (California group). In the third treatment, birds were provided feed and water ad libitum for one day with 8 h light. During day 2-3, feed and water were withdrawn. On 4th day water was provided but no feed was given. On 5 to 49 days, birds were offered feed 27 g each till egg production was reached upto 1%. Water was provided ad libitum. Full feed at the rate of 112 g each bird was offered from day 50 onward. Birds received 8 h of light till 49 days which was increased to 16 h on 50th day onwards (Washington group). The last group served as control. Body weight, egg production, egg size, internal egg quality, shell weight and mortality were determined. Total circulating leukocytes and differential leukocyte counts were also measured. The results demonstrated that induced molting significantly increased egg production from 65 to 75 to 81%, Haugh units from 80.1 to 85.6 to 87.0 and shell weight from 5.4 g to 6.3 to 6.5 g when compared to control. The total circulating leukocytes was significantly lower in molted hens than in control hens. Differential leukocyte counts were affected by all induced molting programs and the heterophil to lymphocyte ratio was significantly increased, reaching 0.60, whereas that of controls was only 0.19.